Nutritional and immunisation status of children visiting hospital during COVID-19 pandemic in Kathmandu, Nepal - Kayastha, Pawana; Chikanbanjar, Vijaya Kumar; Panday, Rajesh Kumar; Manandhar, Sunil Raja (Journal of Kathmandu Medical College, 2022)
Background: The coronavirus disease-2019 (COVID -19) outbreak and lockdown measures have given challenges related to food production, food supply chain, indulgence in low healthy processed food, lack of public transportation, difficulties in accessing emergency and regular health services. Nepal already has high burden of child mortality (39 deaths per 1000 live births) and this pandemic situation has put children at greater risk of facing hunger, malnutrition, lack of routine immunisation, communicable disease outbreak, and many more psychological as well as physical health issues. Objectives: This study identifies nutritional status and gap in routine vaccination in children during COVID-19 pandemic thereby help in modelling action plan to prevent an outpouring in malnutrition and vaccine preventable infections in children. Methods: This is a hospital-based analytical cross-sectional study done among 138 children of ages one to 59 months old from 1st January 2021 to 1st August 2021 attending paediatric clinic of KMCTH. Results: In this study, 20 (14.4%) of the children were stunted, 23 (16.6%) were wasted and 15 (10.8%) were categorised under undernutrition, three (2.2%) were overweight and three (2.2%) were obese. There were significantly more male children stunted than female (p-value = 0.005). Thirty-five (33.3%) of less than 15 months children were reported to have delay of more than two weeks in routine immunisation of children. A significant delay of more than four weeks was observed in 29 (27.6%). Conclusion: Indirect impact of COVID-19 pandemic in children like malnutrition and gap in routine vaccination needs to be addressed seriously in Nepal.